Improving detection and genetic counseling in carriers of spinal muscular atrophy with two copies of the SMN1 gene. (16th July 2013) - Alías, L.; Barceló, M.J.; Bernal, S.; Martínez‐Hernández, R.; Also‐Rallo, E.; Vázquez, C.; Santana, A.; Millán, J.M.; Baiget, M.; Tizzano, E.F.
<x xml:space="preserve">Abstract</x> Spinal muscular atrophy (SMA) is an autosomal recessive disease caused by mutations in the survival motor neuron1 gene (SMN1). Global carrier frequency is around 1 in 50 and carrier detection is crucial to define couples at risk to have SMA offspring. Most SMA carriers have one SMN1 copy and are currently detected using quantitative methods. A few, however, have two SMN1 genes in cis (2/0 carriers), complicating carrier diagnosis in SMA. We analyzed our experience in detecting 2/0 carriers from a cohort of 1562 individuals, including SMA parents, SMA relatives, and unrelated individuals of the general population. Interestingly, in three couples who had an SMA child, both the parents had two SMN1 copies. Families of this type have not been previously reported. Our results emphasize the importance of performing a detailed carrier study in SMA parents with two SMN1 copies. Expanding the analysis to other key family members might confirm potential 2/0 carriers. Finally, when a partner of a known carrier presents two SMN1 copies, the study of both parents will provide a more accurate diagnosis, thus optimizing genetic counseling.